2014
DOI: 10.1002/glia.22684
|View full text |Cite
|
Sign up to set email alerts
|

The complex morphology of reactive astrocytes controlled by fibroblast growth factor signaling

Abstract: Astrocytes are the most abundant cell-type of the human brain and play a variety of roles in brain homeostasis and synaptic maturation, under normal conditions. However, astrocytes undergo dramatic pathological changes in response to brain injury, such as reactive gliosis and glial scar formation. Although abnormal hypertrophy and massive proliferation of astrocytes are obvious, the molecular identity and cues that dictate the structural changes in reactive astrocytes remain unclear. This study proposes that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 57 publications
3
57
0
1
Order By: Relevance
“…These results support the hypothesis that increased number or volume of glia may contribute to the increased brain size commonly observed in patients with RASopathies (31). The altered morphology that we observed is consistent with recent reports that FGF signaling, which acts through Ras signaling and other receptor tyrosine kinases (35), controls astrocyte complexity and morphology (65, 66). We then determined the consequences of this early Ras-specific maturation upon neuronal function.…”
Section: Discussionsupporting
confidence: 92%
“…These results support the hypothesis that increased number or volume of glia may contribute to the increased brain size commonly observed in patients with RASopathies (31). The altered morphology that we observed is consistent with recent reports that FGF signaling, which acts through Ras signaling and other receptor tyrosine kinases (35), controls astrocyte complexity and morphology (65, 66). We then determined the consequences of this early Ras-specific maturation upon neuronal function.…”
Section: Discussionsupporting
confidence: 92%
“…Secondary astrocytes with a purity of 95% were used in the following experiments. The cells were administrated of FGF2 (30 ng/ml) and AG490 (50 μM) for 48 h based on the previous reports, respectively (Kandalam et al, 2012;Kang et al, 2014).…”
Section: Primary Astrocytes Preparation and Drug Administrationmentioning
confidence: 99%
“…mTORC1 Regulates Neuron-derived FGF-2 to Suppress Reactive Astrogliosis-Because it has been suggested that FGF signaling may be necessary for controlling astrocyte morphology and activation (31), one possibility is that extracellular FGF-2 reacts with the FGF-2 receptor on astrocytes in Raptor nKO mice. To confirm the regulation of FGF-2 by mTORC1, we verified the transcriptional levels of FGF-2 and other crucial FGF family members (32) in neurons cultured from mutant or wild type mice.…”
Section: Deletion Of Raptor In Mature Neurons Induces Reactivementioning
confidence: 99%